Improvement of the mechanical properties of SiC reticulated porous ceramics with optimized three-layered struts for porous media combustion. Issue 4 (March 2017) - Liang, Xiong; Li, Yawei; Liu, Jun; Sang, Shaobai; Chen, Yuanyuan; Li, Benwen; Aneziris, Christos G.
Abstract: Silicon carbide reticulated porous ceramics (SiC RPCs) with three-layered struts were fabricated by polymer replica method, followed by infiltrating alumina slurries containing silicon (slurry-Si) and andalusite (slurry-An), respectively. The effects of composition of infiltration slurries on the strut structure, mechanical properties and thermal shock resistance of SiC RPCs were investigated. The results showed that the SiC RPCs infiltrated with slurry-Si and slurry-An exhibited better mechanical properties and thermal shock resistance in comparison with those of alumina slurry infiltration, even obtained the considerable strength at 1300 °C. In slurry-Si, silicon was oxidized into SiO2 in the temperature range from 1300 °C to 1400 °C and it reacted with Al2 O3 into mullite phase at 1450 °C. Meantime, the addition of silicon in slurry-Si could reduce SiC oxidation of SiC RPCs during firing process in contrast with alumina slurry. With regard to slurry-An, andalusite started to transform into mullite phase at 1300 °C and the secondary mullitization occurred at 1450 °C. The enhanced mechanical properties and thermal shock resistance of SiC RPCs infiltrated alumina slurries containing silicon and andalusite were attributed to the optimized microstructure and the triangular zone (inner layer of strut) with mullite bonded corundum via reaction sintering. In addition, the generation of residual compressive stress together with better interlocked needle-like mullite led to the crack-deflection in SiC skeleton, thus improving the thermal shock resistance of obtained SiC RPCs.